PENGGUNAAN PANEL RINGAN UNTUK PAGAR PEMBATAS LINGKUNGAN PERUMAHAN BANJAR WIJAYA RW 07 KELURAHAN CIPETE, KECAMATAN PINANG, KOTA TANGERANG - Kushartomo, Widodo; Hauwendy; Boenyamis, Michael Silvester; Tanurahardja, Edward Mahendra; Christopher (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
Concrete panel fences installed at locations aim to limit land ownership from one another, provide visual protection for the object being fenced and provide a feeling of security to the land owner. The Banjar Wijaya housing complex, especially RW 07, Cipete Village, Pinang District, Tangerang City borders residential areas which are separated by concrete panel fences. The guardrail that divides the RW 07 neighborhood from residents is approximately 500 m long. In several locations of the guardrail, there was damage to the fence, such as broken, missing and holes. Residents' difficulties in finding cheap quality concrete panel fences in the sense of being strong and light, can be overcome by using lightweight concrete panels which are the result of research from the Concrete Construction and Technology Laboratory of Tarumanagara University's Civil Engineering Undergraduate Study Program. The PkM Team from Tarumanagara University's Civil Engineering Undergraduate Study Program guided the manufacture of lightweight concrete panel prototypes which can then be carried out by the community themselves. The implementation of PkM activities was carried out together with the local community, which included preparation for making light panels and installing them.